2023
DOI: 10.1371/journal.pone.0285283
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isocaloric, energy-restrictive, KETOgenic diet on metabolism, inflammation, nutrition deficiencies and oxidative stress in women with overweight and obesity (KETO-MINOX): Study protocol

Abstract: Obesity is considered one of the biggest health problems of the 21st century, becoming a worldwide epidemic, leading to the development of many diseases and increasing the risk of premature death. The first step in reducing body weight is a calorie-restricted diet. To date, there are many different diet types available, including the ketogenic diet (KD) which is recently gaining a lot of attention. However, all the physiological consequences of KD in the human body are not fully understood. Therefore, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…(2) Ketogenic diet: The benefits of fasting can potentially be obtained by following a ketogenic diet characterized by low carbohydrate intake and a high proportion of fat, which is thought to mimic certain aspects of starvation by inducing a shift in whole-body metabolism toward increased fat oxidation and the production of ketone bodies [37]. There are various types of ketogenic diets 4 : 1, 3 : 1, 2 : 1 based on the lipid: carbohydrate ratio [38].…”
Section: Strategies To Modulate Beta-hydroxybutyratementioning
confidence: 99%
“…(2) Ketogenic diet: The benefits of fasting can potentially be obtained by following a ketogenic diet characterized by low carbohydrate intake and a high proportion of fat, which is thought to mimic certain aspects of starvation by inducing a shift in whole-body metabolism toward increased fat oxidation and the production of ketone bodies [37]. There are various types of ketogenic diets 4 : 1, 3 : 1, 2 : 1 based on the lipid: carbohydrate ratio [38].…”
Section: Strategies To Modulate Beta-hydroxybutyratementioning
confidence: 99%
“…The analysis of the clinical trial database (clinicaltrial.gov) indicated that there are two ongoing studies evaluating the effect of KD on OS and mitochondrial functions in subjects with obesity. In the first study, the study protocol of which can be found in my previous work [Drabińska et al, 2023], the OS markers, including MDA, uric acid, SOD, F 2 -IsoPs and 8-oxo-dG, will be analyzed in samples collected from 80 women following KD for 8 weeks. The second study will measure mitochondrial functions and OS in 63 participants with obesity divided into four groups: (1) KD group; (2) calorie-restricted standard diet group; (3) intermittent fasting 16/8; and (4) usual diet [U.S. National Institutes of Health, 2023].…”
Section: Single Electron Transfer (Set) Mixed (Primary Set Secondary ...mentioning
confidence: 99%